Opening remarks. A few words about the conference - О.В. Легостаєва; М.І. Орлюк (Геофизический журнал, 2025)
The International Scientific Conference "CURRENT PROBLEMS OF GEOPHYSICS" (April 22-23, 2025) is dedicated to the 90th anniversary of the outstanding Ukrainian geophysicist, geologist, specialist in the theory of interpretation of potential fields, twice laureate of the State Prize of Ukraine in the field of science and technology, Honored Scientist of the Ukrainian SSR, laureate of the S.I. Subbotin Prize of the NAS of Ukraine, Director of the S.I. Subbotin Institute of Geophysics of the NAS of Ukraine (1992-2021), Doctor of Physical and Mathematical Sciences, Professor, Academician of the NAS of Ukraine Vitaliy Ivanovich Starostenko.